(untitled) (Journal of Economic Research & Business Administration, 2015)
Agglomerations formation process is one of the most perspective economic policy priorities for Regional Development of the Republic of Kazakhstan. They are the basis of formation and development of innovation-oriented economy, concentrating a significant portion of the scientific, educational, industrial and intellectual potential of the country, which can be integrated into the various interactions: regional, national and global. In this regard, this article discusses the significance of the current state of development of cities in the Republic of Kazakhstan as sinter formations, which is evidence-based and supported by relevant statistical data, analyzes their potential for development on the demographic and economic indicators. There are matrices of competitive advantages in terms of the development of local agglomerations as industrial, tourism, transport and logistics as well as cultural centers of the country , with key development strategy at current moment designed and constructed in this article.